Optimalisasi Website Dalam Pelayanan Aqiqah Di Nurul Hayat Surabaya - Xavier Mochamad Yanwar Martias; Airlangga Bramayudha (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2023)
This research was conducted to find out how to optimize the website in aqiqah services in Nurul Hayat Surabaya. This is because, now digital marketing, and e-commerce become one of the demands of technological advancements.In this study, researchers used qualitative descriptive research methods. This method is used to research in depth the optimization activities of the website in aqiqah services in Nurul Hayat Surabaya. Researchers use data collection techniques by conducting interviews, observations, and documentation. In this study, researchers have obtained the results that is. First, Aqiqah Nurul Hayat website applies the concept of userable. Thus, the type of website used is a commercial website with a simple, lightweight, and informative design. Second, Aqiqah Nurul Hayat uses survey methods to measure and know the effectiveness of the methods used. Third, Aqiqah Nurul Hayat prioritizes the use of SEO in the process of optimizing its website.